Political dynasties and poverty: measurement and evidence of linkages in the Philippines - Mendoza, Ronald U (Archīum Ateneo, 2016)
Political dynasty refers to a situation in which an incumbent official has at least one relative in elected office in the past or the present government. In the Philippines, for example, political dynasties comprise over 70% of its Congress. The impact of political dynasties on socioeconomic outcomes such as poverty is an important empirical question (do political dynasties exacerbate poverty?), and this paper presents some evidence. The analysis of data from the Philippines finds a worsening effect of political dynasties on poverty in provinces outside Luzon.